2015
DOI: 10.1038/srep08616
|View full text |Cite
|
Sign up to set email alerts
|

Tonsil-derived Mesenchymal Stem Cells Ameliorate CCl4–induced Liver Fibrosis in Mice via Autophagy Activation

Abstract: Liver transplantation is the treatment of choice for chronic liver failure, although it is complicated by donor shortage, surgery-related complications, and immunological rejection. Cell transplantation is an alternative, minimally invasive treatment option with potentially fewer complications. We used human palatine tonsil as a novel source of mesenchymal stem cells (T-MSCs) and examined their ability to differentiate into hepatocyte-like cells in vivo and in vitro. Carbon tetrachloride (CCl4) mouse model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
89
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 39 publications
3
89
1
Order By: Relevance
“…These data were in accordance with a recent study claiming that MSCs are cleared in CCl 4 -damaged livers by 7 days post-transplantation [39] and support the cell-free mechanism of transplanted ADHLSCs in that liver fibrosis model.…”
Section: Discussionsupporting
confidence: 92%
“…These data were in accordance with a recent study claiming that MSCs are cleared in CCl 4 -damaged livers by 7 days post-transplantation [39] and support the cell-free mechanism of transplanted ADHLSCs in that liver fibrosis model.…”
Section: Discussionsupporting
confidence: 92%
“…Although we recently reported that TMSC alone greatly improved liver function in model rats with liver damage induced by concanavalin A [31] or CCl 4 [32], our current data clearly show an important role for use of scaffolds such as Matrigel in recovering parathyroid function in PTX rats. Indeed, without Matrigel, TMSC did not improve parathyroid cell function, suggesting that scaffold and/or its communication with TMSC is likely to determine the success of stem cell therapy, at least in our disease model.…”
Section: Discussioncontrasting
confidence: 58%
“…According to the reports by our group and others, T-MSCs exhibit typical expression patterns of MSC surface markers (negative for CD14, CD34, and CD45; positive for CD73, CD90, and CD105) and have multilineage differentiation potential [14,15,16,17,40]. Previous studies also emphasized the relatively short doubling time of T-MSCs (about 38 h) compared with other types of MSCs (14–17).…”
Section: Discussionmentioning
confidence: 94%